If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7d + -2 = 14d + -9 Reorder the terms: -2 + 7d = 14d + -9 Reorder the terms: -2 + 7d = -9 + 14d Solving -2 + 7d = -9 + 14d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-14d' to each side of the equation. -2 + 7d + -14d = -9 + 14d + -14d Combine like terms: 7d + -14d = -7d -2 + -7d = -9 + 14d + -14d Combine like terms: 14d + -14d = 0 -2 + -7d = -9 + 0 -2 + -7d = -9 Add '2' to each side of the equation. -2 + 2 + -7d = -9 + 2 Combine like terms: -2 + 2 = 0 0 + -7d = -9 + 2 -7d = -9 + 2 Combine like terms: -9 + 2 = -7 -7d = -7 Divide each side by '-7'. d = 1 Simplifying d = 1
| 15c^2+60=45 | | 5a+6b=50 | | 8-(-9/4) | | -25-2x=-108-8x | | 8-9/4 | | 6b+12=b+42 | | -[9z-(12z+8)]=8+(2z+10) | | 8x+2.4=7.2 | | 4x-9y-7x+5y= | | -5x+2=-4(2x+4) | | -9x-26=-80 | | 15(x+8)=180 | | x+4/8=x-2/6 | | 12-8n=14 | | -45-7x=-115 | | 7e+118=19e+10 | | -45-2x=14-10x | | 25-8x=129 | | d/2-1.3 | | 6a-9=a+46 | | 57=15-6x | | 3r+24/9=5r-30/5 | | 1/3(12p+9)-(p-4) | | 4x/3(2x-4)=48 | | 3x-37=14 | | 1/2(12p+9)-(p-4) | | 3v+29=5v+7 | | 7x+6=26 | | 23-6x=-37 | | 2x+4(10-x)=28 | | -5x+2=-4(2y+4) | | 8n+62=13n+2 |